Does Fish Oil Have an Anti-Obesity Effect in Overweight/Obese Adults? A Meta-Analysis of Randomized Controlled Trials - Du, Shichun; Jin, Jie; Fang, Wenjun; Su, Qing (PloS one, 2015)
Accumulating evidence has suggested favorable effects of fish oil on weight loss in animal experiments; however, findings remain inconsistent in humans. The meta-analysis was performed to investigate the influence of fish oil on some parameters of body composition in overweight/obese adults. Human randomized, placebo-controlled trials were identified by a systematic search of Embase, PubMed, the Cochrane Library, web of science and reference lists of related reviews and articles. The random-effects model was used to estimate the calculated results. In total, 21 studies with 30 study arms were included in this analysis. Calculated results of the meta-analysis demonstrated that fish oil had no effect on reducing body weight (overall SMD = -0.07, 95% CI -0.21 to 0.07, P = 0.31) and BMI (overall SMD = -0.09, 95% CI -0.22 to 0.03, P = 0.14) whether alone or combined with life modification intervention in overweight/obese subjects. However, waist circumference was significantly reduced (SMD = -0.23, 95% CI -0.40 to -0.06, P = 0.008) in those with fish oil supplementation combined with life modification intervention. Waist hip ratio (WHR) was significantly reduced (overall SMD = -0.52 95% CI -0.76 to -0.27, P < 0.0005) in fish oil supplemented individuals with or without combination life modification intervention. Current evidence cannot support an exact anti-obesity role of n-3 polyunsaturated fatty acids (PUFAs) in overweight/obese subjects. However, these subjects may benefit from reducing abdominal fat with fish oil supplementation especially when combined with life modification intervention. Further large-scale and long-term clinical trials are needed to gain definite conclusions.